2015
DOI: 10.3141/2514-12
|View full text |Cite
|
Sign up to set email alerts
|

Crash Patterns at Signalized Intersections

Abstract: Traffic signals are often implemented to provide for efficient movement and to improve traffic safety. Nevertheless, severe crashes still occur at signalized intersections. This study aims to improve understanding of signalized intersection safety by identifying crash types, locations, and factors associated with signalized intersections. For this purpose, 1,295 police-reported crashes at 87 signalized intersections were analyzed on the basis of detailed crash descriptions, that is, crash data and collision di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 28 publications
0
20
0
Order By: Relevance
“…Similar research has been conducted (e.g. Polders et al, 2015;Plavsic, 2010;Molinero Martinez et al, 2008;INTERSAFE, 2005;Wiltschko, 2004), however, the usage of k-medoids clustering and association rules in this context is novel.…”
Section: Safety At Road Junctionsmentioning
confidence: 57%
See 1 more Smart Citation
“…Similar research has been conducted (e.g. Polders et al, 2015;Plavsic, 2010;Molinero Martinez et al, 2008;INTERSAFE, 2005;Wiltschko, 2004), however, the usage of k-medoids clustering and association rules in this context is novel.…”
Section: Safety At Road Junctionsmentioning
confidence: 57%
“…Van Maren (1980) reported that (multi-lane) unsignalized intersections have a lower number of crashes per million conflicts than signalized intersections. For signalized intersections, it was found that the dominant crash types are rear-end and head-on collisions (Polders et al, 2015;Obeng, 2007), however, Abdel-Aty et al (2006 states that this also depends on the number of lanes and traffic volumes. In comparison to that, the majority of unsignalized intersection accidents are angle collisions (e.g.…”
Section: Safety At Road Junctionsmentioning
confidence: 99%
“…Some risk factors may be shared between emergency and general motor vehicle crashes, although emergency vehicle drivers have different driving behaviors due to "code 3 running," and some emergency vehicles have unique performance characteristics. Examples of the shared risk factors are intersection encounters (Kahn et al, 2001;Polders, Daniels, Hermans, Brijs, & Wets, 2015), drivers' experience (Becker, Zaloshnja, Levick, Li, & Miller, 2003;Retting, Ulmer, & Williams, 1999), drivers' distraction (Horberry, Anderson, Regan, Triggs, & Brown, 2006;Kaber, Liang, Zhang, Rogers, & Gangakhedkar, 2012), and geometrical road design and arrangement (Abdel-Aty & Wang, 2006;Tay & Rifaat, 2007). An analysis of risk factors associated with general motor vehicle crashes that may be relevant to emergency vehicle operation may provide further insight for emergency vehicle crash reduction as well as for comparisons between public motor driving and emergency vehicle driving.…”
Section: Association Between Emergency Vehicle Crashes and General Momentioning
confidence: 99%
“…The size of intersections has a significant impact on vehicle safety. Intersections with more lanes increase the likelihood of traffic conflicts; a vehicle travels longer distances in the box junction (a place where two roads cross), encountering more traffic that travels in the same and different directions (Poch & Mannering, 1996;Polders et al, 2015;Wang, Abdel-Aty, & Brady, 2006). Heavy and large vehicles that cannot make rapid maneuvers (such as deceleration) may experience additional challenges while passing through such intersections.…”
Section: Environment Factorsmentioning
confidence: 99%
“…Both red light running and speeding are considered to be substantive problems, frequently leading to collisions. Collisions caused by red light running are typically associated with side impacts (Garber et al, 2007;Polders et al, 2014). Red light running at signalized intersections has a significant impact on road safety since this leads to more serious collisions, being side collisions or collisions with vulnerable road users (Kloeden et al, 2001;Retting et al, 1999a,b;Shin and Washington, 2007).…”
Section: Introductionmentioning
confidence: 99%